A Tri‐Channel Oxide Transistor Concept for the Rapid Detection of Biomolecules Including the SARS‐CoV‐2 Spike Protein. Issue 3 (18th November 2021) - Lin, Yen‐Hung; Han, Yang; Sharma, Abhinav; AlGhamdi, Wejdan S.; Liu, Chien‐Hao; Chang, Tzu‐Hsuan; Xiao, Xi‐Wen; Lin, Wei‐Zhi; Lu, Po‐Yu; Seitkhan, Akmaral; Mottram, Alexander D.; Pattanasattayavong, Pichaya; et al.
Abstract: Solid‐state transistor sensors that can detect biomolecules in real time are highly attractive for emerging bioanalytical applications. However, combining upscalable manufacturing with the required performance remains challenging. Here, an alternative biosensor transistor concept is developed, which relies on a solution‐processed In2 O3 /ZnO semiconducting heterojunction featuring a geometrically engineered tri‐channel architecture for the rapid, real‐time detection of important biomolecules. The sensor combines a high electron mobility channel, attributed to the electronic properties of the In2 O3 /ZnO heterointerface, in close proximity to a sensing surface featuring tethered analyte receptors. The unusual tri‐channel design enables strong coupling between the buried electron channel and electrostatic perturbations occurring during receptor–analyte interactions allowing for robust, real‐time detection of biomolecules down to attomolar (am ) concentrations. The experimental findings are corroborated by extensive device simulations, highlighting the unique advantages of the heterojunction tri‐channel design. By functionalizing the surface of the geometrically engineered channel with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) antibody receptors, real‐time detection of the SARS‐CoV‐2 spike S1 protein down to am concentrations is demonstrated in under 2 min in physiological relevant conditions. Abstract : A solution‐processed metal oxide heterojunction channel with a geometrically engineered tri‐channel architecture several millimeters in size, is developed and used as a generic platform for robust, selective, and ultrasensitive detection of various biomolecules. As a proof‐of‐concept, selective sensing of the SARS‐CoV‐2 spike protein down to attomolar concentrations in under 2 min is demonstrated.